UJI BERBAGAI TINGKAT KETINGGIAN PERANGKAP FEROMON TERHADAP KETERTARIKAN KUMBANG KELAPA oryctes rhinoceros L PADA TANAMAN KELAPA SAWIT - parno, parno; hendarti, indri; sarbino, sarbino (Jurnal Sains Mahasiswa Pertanian, 2017)
TEST OF VARIOUS ALTITUDE LEVEL OF PHEROMONES TRAP TOWARDS RHINOCEROS BEETLES’ Oryctes rhinoceros LINTEREST TO THE PALM PLANT Parno1) Indri Hendarti2) Sarbino2) 1) College Student of Agriculture Faculty , 2) Lecturer of Agriculture Faculty Tanjungpura University Pontianak     ABSTRACT Oryctes rhinoceros L (Coleoptera) or a rhinoceros beetle is one of the important pests in oil palm plantations. These pests can reduce the production of fresh fruit bunches (FFB) in the first year to produce up to 69%, and even it causes the death of young plants up to 25%. The purpose of this study was to find the altitude level of appropriate pheromone traps for the rhinoceros beetles. This Research was conducted at the Oil Palm Plantation of PT. Rajawali Jaya Perkasa, Tanjungwangi Village, Rasau Jaya district, Kubu Raya Regency. The study was conducted for approximately 4 months. The research included 5 treatments with 5 repititions, the tested treatments are: High-trapping 1, 2, 3, 4 and 5 meters. The observed variable was the number of O.rhinoceros trapped, the number of males and females O. rhinoceros trapped, and the intensity of the attacks. The results showed that the number of beetles are mostly trapped at a height of 3 meters in amount of 103 rhinoceros beetles/month and at least 53 rhinoceros beetles/month at a height of 5 meters. Female beetle quantities were caught more than the male beetles. At the beginning of treatment, there was no difference in the intensity of the attacks and at the end of the treatment, the average intensity of the attacks which reached 30.8% was classified as medium criteria.     Keywords: Oryctes rhinoceros, Palm, Pheromones.